Exploring the impact of influencer marketing on Gen Z and Millennial consumers within the financial services industry. - Johnson, Chelsea (The IIE, 2023)
This study investigated the influence of influencer marketing on Gen Z and Millennial consumers in the financial services industry. The financial industry has been slow to adopt social media and influencer marketing in their campaigns, a notable opportunity for this industry. In the digital age, where social media influencers hold substantial sway on consumer’s behaviour, comprehending the intricacies of influencer marketing is vital for financial institutions aiming to engage these younger generations. Through an extensive review of literature and qualitative interviews with both generational cohorts, this research explored the pivotal role influencers play in shaping the financial behaviour and decision-making processes of Gen Z and Millennial consumers. Key findings emphasise the critical factors affecting the efficacy of influencer marketing campaigns in the financial services sector. It is evident that influencers must possess characteristics of relevance, relatability, credibility, and trustworthiness when promoting financial brands to both Gen Z and Millennial consumers. The study underscores the importance of aligning influencer partnerships with the values, aspirations, and financial needs of Gen Z and Millennial consumers. This study concluded that successful influencer marketing strategies in the financial industry must establish genuine connections and deliver valuable content that resonates with the unique preferences and concerns of both cohorts. One of the primary contributions of this study lies in its exploration of the factors that influence consumer behaviour within the context of influencer marketing in the financial industry. This research provides practical insights into optimising social media marketing strategies, particularly on Instagram, for engaging Gen Z and Millennial consumers.
Keywords: Social Media; Financial Literacy; Brand Awareness; Brand Loyalty; Consumer-Based Brand Equity (CBBE); Buying Behaviour